The impact of Basel III on lending behaviour (credit extension) of South African banks in relation to small medium enterprises (SMEs) - Ramere, Thapelo Joseph (My University, 2018)
ABSTRACT Banking has developed rapidly over the past few years. In 2007, the Basel Committee On Banking Supervision (BCBS) introduced Basel II to align regulatory capital with the actual underlying risks as such improving banks’ ability to absorb losses. However, the 2008 Bank crisis that originated in the United States of America (USA) and later progressed to the European banking sector revealed that banks did not have sufficient quantity and quality of capital and liquidity to absorb losses and that they could increase leverage without breaching the regulatory capital requirements. This Bank crisis exposed weaknesses in the global bank regulations as it revealed that it lacks development in the banking sector. The Basel III Accord was introduced across the globe in 2013. It sought to improve the banks’ ability to absorb losses. Basel III would be implemented over a seven-year period, from January 2013 to December 2019. This study investigates the impact of introducing capital requirements under Basel III banking regulation. Specifically, how it affects access to funding for SMEs. Access to funding for these entities is scarce thus, an important inquiry is whether Basel III capital requirement advances or worsens the situation in South Africa. The investigation undertook to achieve three objectives i) To establish how South African banks respond to changes in capital requirements and assess trends in the capital ratio. ii) To examine whether banks respond to capital requirement changes by changing Risk Weighted Assets (RWA) or by adjusting capital or both and in particular to analyse whether banks reduce exposure to assets and loans that are an important source of funding for SMEs. iii) To assess trends in Exposure at Default (EAD), in particular to analyse whether banks’ exposure has shifted away from SMEs. iii Three empirical findings and the discussion in this study found evidence that banks reduced their exposure to SMEs in the two years before the implementation of Basel III, a phase called Preparatory Phase. Policy makers need to take note that although activities of SMEs are classified as high risk in the banking sector they are vital for economic growth. SMEs depend largely on bank funding: as such, any reduction will result in failure of some SMEs. This classification has led to banks reducing lending to SMEs and if this trend continues, South Africa will not be able to realise its objective to improve the SMEs role in the economy and its role will diminish.
MBA Thesis
Keywords: Basel III (2010) Small business -- Finance. Banks and banking -- South Africa.